Application of Indonesian National Standard 03-2834-2000 in Enhancing Concrete Design Skills for Vocational Construction Teachers - Putra, Riansyah; Wijaya, Kinanti; Sutrisno, Sutrisno; Tinov, Naufal; Dwi Putri, Mita; Hutria, Wahyu (Universitas Putra Indonesia YPTK Padang, 2025)
The main challenge identified during the community service program was the limited experience of vocational teachers in effectively utilizing the available concrete design laboratory equipment at the school. This limitation has hindered the effective delivery of practical learning in concrete design, resulting in suboptimal skill development among students and reduced alignment with industry standards. This community service program contributed to enhancing vocational teachers’ competence in applying SNI 03-2834-2000 through hands-on training and mentoring on the effective use of concrete design laboratory equipment in SMKN 2 Medan. The community service program was conducted through several stages, including field needs analysis, development of a technical guidance manual, initial socialization, mentoring sessions, and evaluation of the resulting concrete design projects. The results of the community service program showed that the training participants successfully understood the steps of concrete design in accordance with the established standards, as evidenced by an evaluation involving 22 participants which indicated an average achievement score of 89% across the aspects of ease of use, usefulness, attractiveness, and satisfaction. In conclusion, the program effectively strengthened vocational teachers’ competence in concrete design based on SNI 03-2834-2000, and its implementation model can be replicated in other vocational schools to enhance the quality of practical construction learning.